Peranan Orang Percaya Dalam Pelayanan Diakonia Dimasa Pandemi Covid-19 - John Abraham Christiaan; Yusup Heri Harianto; Simon Simon (Sekolah Tinggi Teologi Nusantara, 2022)
Since the establishment of Coronavirus Disease 2019 (Covid-19) as a pandemic, the Indonesian government must adopt specific policies to prevent and break the chain of the Covid-19 spread. Such policies have significantly but negatively influenced people’s activities, particularly in the economic sector. The most affected class is those having low income or weak economic conditions. This problem is also experienced by many churches and church deacons. In facing this kind of situation, believers who have better economic capacity are required to take an active role by helping and funding the church’s treasury and assisting the church deacons. The results showed that the Covid-19 pandemic greatly affects the people’s economic condition including the declining church fund because all worship activities must be done online. However, one thing that pleases God and humans is that in such a situation, many believers and churches are still willing to serve the community in the deacons’ service tasks. The believers play an active role in funding the church’s treasury, and then the church sets the cash aside for diaconal services to the affected church and non-church community members by providing food, vitamins, and medicines. It is a reflection of the service that God wants. AbstrakSejak ditetapkanya Coronavirus Disease 2019 (Covid-19) sebagai pandemi, pemerintah Indonesia harus mengambil kebijakan untuk mencegah dan memutus matarantai penyebaran Covid19. Dengan adanya kebijakan pemerintah, kegiatan masyarakat menurun drastis termasuk sektor ekonomi dan yang paling terdampak adalah kondisi perekonomian yang rendah. Kondisi ini juga dialami oleh beberapa gereja dan warga diakonia gereja. Dalam situasi demikian, orang percaya yang memiliki kemampuan ekonomi dituntut untuk berperan aktif melakukan kegiatan dengan membantu mengisi kas jemaat, da membantu dikonia gereja. Dari hasil Penelitian disimpulkan bahwa; masa pandemi Covid-19 berdampak pada kondisi perekonomian masyarakat termasuk menurunya kas gereja karena kegiatan ibadah dilakukan secara online. Sekalipun situasi sulit itu banyak orang percaya dan gereja tergerak untuk melayani masyarakat dalam tugas pelayanan diakonia. Cara-cara yang ditempuh orang percaya adalah berperan aktif mengisi kas gereja, kemudian gereja menyisihkan kas untuk pelayanan diakonia kepada warga gereja, dan warga masyarakat non gereja terdampak dengan turun langsung ke lapangan untuk memberikan bantuan bahan makanan, vitamin dan obat-obatan. Hal ini tentu menjadi suatu cermin pelayanan yang dikehendaki Tuhan. Kata Kunci: Diakonia, Pandemi Covid-19. Pelayanan, orang Percaya.